The Effectiveness of the Lesson Study Course ‎based on the Interconnected Model of ‎Professional Growth (IMPG) in Developing ‎Female Science Teachers’ Instructional ‎Performance and Academic Achievement of ‎their Students - Al-Hraziah, Bothaina; Embosaidi ‎, Abdullah; Al- Al-khrosi‎, Hussien (Jordan Journal of Educational Sciences, 2024)
This study aimed to investigate the effectiveness of the Lesson Study Course based on the Interconnected Model of Professional Growth in developing the instructional performance of female science teachers and their students in the Sultanate of Oman. The sample of the study consisted of 30 female teachers who teach eighth-grade, distributed equally into two groups: experimental (15) and control (15). In addition, 1775 female students took the achievement test. To achieve the aims of the study, a training manual was prepared, which considered the four domains that make up the Interconnected Model of Professional Growth. The data were collected using two instruments: an observation card which was used to assess the teaching performance of the female teachers. The cards consisted of 32 skills. The validity and reliability of the card were verified, and it was checked at 88.75. An achievement test was administered to students, and both its validity and reliability (0.82) were checked. The results showed a significant difference in the mean scores for both groups in favor of the experimental group in the teaching performance and achievement test. The study concluded with several recommendations and suggestions to improve the classroom practices of female science teachers